Studi Literatur: Efektivitas Konseling Individual Dengan Teknik Reframing Dalam Mengubah Pola Pikir Negatif Remaja - Suci Permata Hati; Yenti Arsini; Lisna Marselina Nasution (Universitas Maritim AMNI Semarang, 2024)
The background of this research is that considering current developments, negative thinking is widespread among teenagers. Negative thinking can affect your environment both in carrying out daily activities and in other ways. This research aims to see the effectiveness of individual counseling using reframing techniques in helping teenagers identify and understand their negative thought patterns, and help them replace them with more positive and constructive thought patterns. The method used in this research is qualitative descriptive analysis. The type of qualitative research used is a literature review. This research uses secondary data with references used from searches of research articles published on the internet. Based on the results of the literature review obtained, reframing techniques have a significant role in changing negative thought patterns in adolescents.